PENGARUH LATIHAN BALLHANDLING TERHADAP PENINGKATAN KEMAMPUAN DRIBBEL PADA SISWA EKSTRAKURIKULER BOLA BASKET SMAN 1 KADUGEDE - Fajar Permana Hidayat; Sartono Sartono (STKIP Melawi, 2025)
Abstract: Examining the impact of ballhandling training on the development of dribbling abilities in students involved in extracurricular basketball activities at SMAN 1 Kadugede was the aim of this research. With a one-group pre-test and post-test design, a quantitative research methodology was used. The sample in this study consisted of 12 students selected purposively. Data collection was conducted through a zig-zag dribbling ability test before and after the ball-handling training program, which lasted four weeks with a training intensity of three times per week. Data analysis showed that the average score rose from 12.66 on the pre-test to 15.41 on the post-test. The data were homogeneous and regularly distributed, according to the findings of the normality and homogeneity tests. The paired sample t-test findings, on the other hand, revealed a significant relationship between ballhandling training and enhanced dribbling skill, with a significance value of 0.000 (< 0.05). To sum up, ballhandling instruction may be a useful strategy for enhancing students' basketball dribbling skills. Keywords : Ballhandling, dribbel, basketball Abstrak: Studi bertujan guna menguji sejauh mana pengaruh latihan ballhandling terhadap peningkatan keterampilan dribbling pada siswa peserta ekstrakurikuler bolabasket di SMAN 1 Kadugede. Dengan desain pra-tes dan pasca-tes kelompok tunggal, metodologi penelitian kuantitatif digunakan. Dua belas siswa yang dipilih secara sengaja menjadi sampel penelitian. Pengumpulan data dilakukan melalui tes kemampuan dribbling zig-zag sebelum dan sesudah program latihan ballhandling yang berlangsung selama empat minggu dengan intensitas latihan tiga kali seminggu. Berdasarkan analisis data, skor rata-rata meningkat dari 12,66 pada pra-tes menjadi 15,41 pada pasca-tes. Temuan studi membuktikan jika data bersifat homogen dan terdistribusi normal. Sementara itu, hasil uji paired sample t-test membuktikan taraf sig. 0,000 (< 0,05) berarti ada pengaruh yang signifikan antara latihan ballhandling dengan peningkatan kemampuan dribbling. Kesimpulannya, kemampuan menggiring bola siswa dalam permainan bola basket dapat ditingkatkan dengan menggunakan latihan dribblimg. Kata kunci : Ballhandling, dribbel, bola basket